2012
DOI: 10.1007/s10508-012-9931-9
|View full text |Cite
|
Sign up to set email alerts
|

Is Sexual Concordance Related to Awareness of Physiological States?

Abstract: Sexual concordance refers to the degree to which two aspects of human sexual arousal (genital response and self-reported sexual arousal) correspond with each other. Researchers have consistently reported a sex difference in sexual concordance: The relationship between genital responses and reported feelings of sexual arousal in men is positive and large, whereas the relationship in women is positive but much smaller than that seen in men. The study of interoception--people's awareness of their physiological st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 35 publications
3
40
1
2
Order By: Relevance
“…There was no significant difference in the number of participants who exhibited high respiration rate awareness between the two studies, χ 2 (1) = 0.003, P = 0.96. Consistent with the results of the chi‐square analysis, the women in the current sample had significantly higher heart rate awareness (M = 0.31, SD = 0.30) than the women in Suschinsky and Lalumière's study (M = 0.11, SD = 0.26), t (49) = 2.45, P = 0.018. There was no significant difference in respiration rate awareness across the two studies, t (49) = 0.14, P = 0.88.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…There was no significant difference in the number of participants who exhibited high respiration rate awareness between the two studies, χ 2 (1) = 0.003, P = 0.96. Consistent with the results of the chi‐square analysis, the women in the current sample had significantly higher heart rate awareness (M = 0.31, SD = 0.30) than the women in Suschinsky and Lalumière's study (M = 0.11, SD = 0.26), t (49) = 2.45, P = 0.018. There was no significant difference in respiration rate awareness across the two studies, t (49) = 0.14, P = 0.88.…”
Section: Resultssupporting
confidence: 84%
“…Suschinsky and Lalumière presented men and women with a variety of short sexual and nonsexual films while their genital response, heart rate, and respiration rate were measured. After each film, participants were asked to estimate their genital response, heart rate, and respiration rate.…”
mentioning
confidence: 99%
“… 27 The available evidence suggests that sexual concordance is not significantly related to performance on typical laboratory measures of interoceptive sensitivity such as HBP (Suschinsky & Lalumière, 2012, 2014). No studies to date have, however, examined the correlation between sexual concordance and performance on real-world measures of interoceptive sensitivity (e.g., Cox et al, 1985).…”
mentioning
confidence: 99%
“…This study found that there is no correlation between RWA and sexual discordance of santri in Indonesia Islamic boarding school. According to Suschinsky and Lalumière (2012), sexual concordance (as the opposite continuum of sexual discordance) is more influenced by individual's consciousness of their physiological condition. This physiological consciousness among others includes consciousness of heart beat and consciousness of their own breathing or respiration.…”
Section: Discussionmentioning
confidence: 99%